2017
DOI: 10.1371/journal.pone.0180333
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phenotypic and functional analysis of migratory dendritic cell subsets from human oral mucosa and skin

Abstract: Antigen exposure to oral mucosa is generally thought to lead to immune tolerance induction. However, very little is known about the subset composition and function of dendritic cells (DC) migrating from human oral mucosa. Here we show that migratory DC from healthy human gingival explants consist of the same phenotypic subsets in the same frequency distribution as DC migrating from human skin. The gingival CD1a+ Langerhans cell and interstitial DC subsets lacked CXCR4 expression in contrast to their cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Lang, 2005;Gibbs and Ponec, 2000;Jiang et al, 2014;Larjava et al, 2011a;Presland and Dale, 2000;Presland and Jurevic, 2002;Vriens et al, 2008). Kroeze et al, 2012). Taken together, these data suggest that oral mucosa epithelium is intrinsically primed to repair through different mechanisms from that observed in skin, but the large number of epithelial cell layers characteristic of many types of oral mucosa subject to extreme mechanical load and pathogen exposure is most probably regulated by extrinsic factors in the microenvironment.…”
Section: Wound Healing After Tooth Extractionmentioning
confidence: 85%
See 1 more Smart Citation
“…Lang, 2005;Gibbs and Ponec, 2000;Jiang et al, 2014;Larjava et al, 2011a;Presland and Dale, 2000;Presland and Jurevic, 2002;Vriens et al, 2008). Kroeze et al, 2012). Taken together, these data suggest that oral mucosa epithelium is intrinsically primed to repair through different mechanisms from that observed in skin, but the large number of epithelial cell layers characteristic of many types of oral mucosa subject to extreme mechanical load and pathogen exposure is most probably regulated by extrinsic factors in the microenvironment.…”
Section: Wound Healing After Tooth Extractionmentioning
confidence: 85%
“…Additionally, the better blood microcirculation in the oral mucosa, enhancing nutrient and inflammatory cell access to the wound site, is considered to be beneficial for wound healing. Both intrinsic properties of the cells within the oral mucosa as well as interactions with the surrounding tissue environment and immune system have been identified, which might in part explain the superior oral wound healing (Barrientos et al, 2008;Boink et al, 2016;Chen et al, 2010;Feller et al, 2013;Glim et al, 2013;Iglesias-Bartolome et al, 2018;Kosten et al, 2015;Kosten et al, 2017;Larjava et al, 2011a;Szpaderska et al, 2005;Szpaderska et al, 2003). Kroeze et al (2012) identified an autocrine feedback loop regulating reepithelialisation through chemokine receptors CCR1, CCR10, CXCR1, CXCR2 and CXCR3 after wounding of the epidermis.…”
Section: Saliva and Crevicular Fluidmentioning
confidence: 99%
“…3,4 The different responses of the skin and oral mucosa to sensitizers are reported to be influenced by various factors, including the tissue structure, innate immune properties, and the infiltration and migration of immune cells. 1,5 The central event in immune sensitization is the presentation of antigen by dendritic cells (DCs) to antigen-responsive T cells in the local lymph node, which results in T-cell priming (memory). The threshold for sensitization is now thought to be tightly regulated by the activation and maturation state of DCs and their cytokine and chemokine products, but also molecules secreted by local keratinocytes and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the basal layer and migrating to the outer surface of the epithelium, epithelial cells proliferate, differentiate and are finally shed into the oral cavity, allowing for effective clearance of pathogens and rapid repair after injury 1 . The healthy oral mucosa also produces antimicrobial peptides, cytokines and chemokines which contribute to preserving the host-microbiota (multi-species biofilm) homeostasis 2 5 . The cellular mechanisms responsible for this notably high epithelial turnover and primed antimicrobial defense of the oral epithelial barrier are still unknown.…”
Section: Introductionmentioning
confidence: 99%